Design and development of acoustic cavitation agents for biomedical and industrial applications - Su, Xiaoqian (Nanyang Technological University, 2021)
Acoustic cavitation has been utilized for biomedical and sonochemical processing due to the immediate physicochemical changes induced by the event. Unfortunately, cavitation often requires immense acoustic pressures to nucleate, resulting in a difficult to control process. Yet, the control of cavitation is pivotal to prevent unwanted and off-target side effects. Exogenous cavitation nuclei (i.e. cavitation agents) have been researched as a means to control cavitation events and reduce the threshold for cavitation. Typically, these nuclei have been micro-/nanobubbles, but literature has recently garnered interest in solid cavitation agents for their ability to enable longer circulation times and improved cavitation activity. Unfortunately, work on solid cavitation agents has been limited to the biomedical field, and advancements in this area are still ongoing. Existing literature demonstrates nanostructured solid cavitation agents for improved drug delivery, and extravasation into tissue; however, these agents have limited loading potential due to the non-biodegradable potential of the particles. Furthermore, the synthesis of these particles has primarily been explored with chemically and biologically inert materials, thereby limiting their interactions with the surrounding environment. Thus, I hypothesized that the physical and chemical effects of cavitation may be controlled by the material and structure of the cavitation agent. Therefore, I explored the various designs of solid cavitation agents for both biomedical and industrial applications in this thesis. I sought out to demonstrate the ability to enhance specific physiochemical changes of the environment resulting from cavitation by tuning the material and structure of the solid cavitation agents. Specifically, I explored and developed three solid cavitation agents comprised of different materials, diameters, and structures, namely 1) biodegradable multi-cavity polymer microparticles, 2) gold nanocones, and 3) fractured hollow-shell metal oxide nanoparticles. By simply considering the physical and acoustic characteristics of these particles, I demonstrated the ability to address specific challenges faced by a broad range of applications. In the first results chapter of this thesis, I explored the potential of micro-/nanostructured, biodegradable multi-cavity polymer particles as cavitation agents. These particles have a tuneable size and morphology to alter the cavitation response of the particle, ultimately permitting enhanced efficiency of drugs and improve the overall biomedical performance in ex vivo and in vivo models. Our work on biodegradable multi-cavity polymer microparticles demonstrated the potential for cavitation-guided implantation of drug-eluting microparticles as a theranostic agent, enhancing imaging contrast whilst improving the local and sustained delivery of therapeutics in atherosclerosis and peripheral artery disease models. Comparatively, gold nanocones and fractured hollow-shell metal oxide nanoparticles can be influenced by the physicochemical changes from cavitation to provide more effective sonocatalysis, thereby enabling alternative (and possibly more sustainable) methods for various chemical reactions. The key conclusion from this thesis is that through material choice and precise structuring of the solid particle, solid cavitation agents can be tailored to address specific challenges presented by both chemical and biomedical processes.